(untitled) (Argos, 2024)
In the well-known first Book of Politics Aristotle deals with some topics in which it is relevant the study of economics and chrematistics (Pol. A 8-11). A key of his argument consists in the distinction of this two matters and, after that, in two kinds of chrematistics (chrematistics1 and chrematistics2). This second distinction is supported by the notion of genuine wealth (or true wealth, ἀληθινὸς πλοῦτος, Pol. A 8, 1256b30-1): chrematistics1 looks for a genuine wealth while chrematistics2 looks for an unlimited quantity of material goods. Our investigation shows that the foundations of genuine wealth is the definition of city: Pol. A 1-2 develops this definition and it is used in the latter chapters, especially in Pol. A 8-11. We defend the general hypothesis that Aristotle uses the first definitions of the beginnings of the Pol. A as genuine explanatory principles and, so, that the whole argument is supported on this definitions as first assumptions.